2010
DOI: 10.1002/pi.2916
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficiency of polymeric solar cells via alignment of carbon nanotubes

Abstract: Carbon nanotubes (CNTs) are well-known electron acceptor materials for use in optoelectronic devices due to their appropriate electronic properties. In this work, we report on their use as a part of the multi-component active layer in organic solar cells to provide better transport of photogenerated charges. To optimize transport, orientation of CNTs perpendicular to the electrodes of solar cells with an active layer of poly(3-hexylthiophene)-CNT-(6,6-phenyl C 61 butyric acid methyl ester) (P3HT-CNT-PCBM) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…SWNTs functionalized with phthalocyanine‐pyrene conjugates have also been utilized by Guldi and coworkers in dye‐sensitized solar cells 77. Two different approaches published by us of this paper, discussed further, show that the use of SWNTs improves the photovoltaic properties of efficient polymer solar cells by structuring the BHJ active layer 78, 79. However, the use of CNTs in organic photovoltaics is not limited to SWNTs as demonstrated by the incorporation of PCBM‐functionalized multi‐walled carbon nanotubes (MWNTs) in PSCs 80.…”
Section: Carbon Nanotubes In Polymer Solar Cellsmentioning
confidence: 82%
See 1 more Smart Citation
“…SWNTs functionalized with phthalocyanine‐pyrene conjugates have also been utilized by Guldi and coworkers in dye‐sensitized solar cells 77. Two different approaches published by us of this paper, discussed further, show that the use of SWNTs improves the photovoltaic properties of efficient polymer solar cells by structuring the BHJ active layer 78, 79. However, the use of CNTs in organic photovoltaics is not limited to SWNTs as demonstrated by the incorporation of PCBM‐functionalized multi‐walled carbon nanotubes (MWNTs) in PSCs 80.…”
Section: Carbon Nanotubes In Polymer Solar Cellsmentioning
confidence: 82%
“…Significant improvement of the I SC of P3 HT:PCBM solar cells has been obtained by the Plastic Optoelectronics Group of Limoges University, adding a small amount (0.1 wt%) of SWNTs in the solution and performing their orientation during the annealing process 79. The initial average cell efficiencies before annealing, around 2.5%, have been enhanced to 4.4% with 10 MHz electric field application.…”
Section: Carbon Nanotubes In Polymer Solar Cellsmentioning
confidence: 99%
“…The PCE can be further enhanced by improving the alignment of CNTs. The orientation of the CNTs can be manipulated by a high-frequency AC electric field [275]. When CNTs was perpendicular to the electrodes, the PCE of the P3HT/CNT/PCBM device approached 4.53%.…”
Section: Cnts As Charge Transport Materials In Oscsmentioning
confidence: 99%
“…8 Using a different strategy based on the alignment of the tubes, Radbeh et al also reported a significant improvement of BHJ solar cells efficiency (4.53% reported). 9 However, despite many attempts, recent systematic studies on acid shortened tubes tend to show that SWCNTs degrade the performances of BHJ solar cells. 10 In the present paper, we report on the achievement of large open circuit voltage V oc over 0.8 V, together with decent fill factor and large short circuit current, through the incorporation of high pressure CO conversion (HiPCO) ester functionalized SWCNT into a poly(3-hexylthiophene) (P3HT): 1-(3-methoxycarbonyl) propyl-1-phenyl [6,6] Preparation of SWCNT-CO 2 H 2 2 SWCNTs 1 of 100 mg were stirred in 100 mL aq.…”
Section: Introductionmentioning
confidence: 99%